THE ROLE OF GAMIFICATION IN ENHANCING LEARNING OUTCOMES IN MATHEMATICS - Joydeb Debnath (IJRDO -JOURNAL OF MATHEMATICS, 2025)
Educators now use gaming methods to create better student participation and knowledge gains in teaching. This research assesses how gamification helps students learn math better by measuring its results on their performance level and engagement. Our study design combines two groups of middle school students where one part learns through a gamified system while the other accepts regular class instruction. Tests before and after the intervention happened, along with student engagement responses and teacher observations. Students who learned math through a game-based system performed better, according to results, with their scores rising 23.6 points, while the other group did not change. Students showed increased drive and participated more when learning with game elements because the method helped them to think deeper. Though the study notes potential problems when using motivation systems and competitive elements in learning, it shows that proper gamified designs work with both types of motivation effectively. Our results show that educational authorities should introduce gamified math learning to make student classes more enjoyable and help students keep their math knowledge. Research needs to evaluate how gamification helps different groups of students retain mathematical knowledge over time. Users and students see digital learning experiences as more exciting and better ways to master new knowledge when games become part of their studies.